Liberation movements and stalled democratic transitions: reproducing power in Rwanda and South Africa through productive liminality. Issue 7 (3rd October 2018) - Beresford, Alexander; Berry, Marie E.; Mann, Laura
ABSTRACT: The lack of convergence towards liberal democracy in some African countries reflects neither a permanent state of political aberration, nor necessarily a prolonged transitional phase through which countries pass once the "right" conditions are met. Examining the cases of two ruling parties, the Rwandan Patriotic Front (RPF) and the African National Congress in South Africa, we develop the concept of productive liminality to explain countries suspended (potentially indefinitely) in a status "betwixt and between" mass violence, authoritarianism, and democracy. On the one hand, their societies are in a liminal status wherein a transition to democracy and socio-economic "revolution" remains forestalled; on the other hand, this liminality is instrumentalized to justify the party's extraordinary mandate characterized by: (a) an idea of an incomplete project of liberation that the party alone is mandated to fulfil through an authoritarian social contract, and (b) the claim that this unfulfilled revolution is continuously under threat by a coterie of malevolent forces, which the party alone is mandated to identify and appropriately sanction.